Access to Quality Education among Students with Special Needs amidst Covid-19: A Review on Challenges and Prospects - Mwamakula, Frank (East African Journal of Education Studies, 2024)
The COVID-19 pandemic created chaos in education management systems as well as teaching and learning across the world. It led to limited global interactions, lockdowns and school closures, which transformed the routine face-to-face to an online mode of teaching and learning. Although all schools, teachers and students were affected, children with special needs suffered a lot in their continuing learning struggles. This systematic review explored 25 papers to create further understanding and interpretations across studies and countries on COVID-19 challenges and prospects for special needs education. The study found that access to education among students with special needs amid Covid 19 was challenging and demanding in terms of resources, teachers’ innovation and creativity as well as community support. The pandemic disrupted normal learning leading to learning loss. Teachers, parents and students with special needs were found to be unprepared for learning continuity during emergencies. Although online learning turned to normal learning, it was insufficient due to technological disparities and the remoteness of some homes. Learning from home is evidenced to be ineffective in less developed areas as it leads to a digital divide among learners. The study has implications for creating awareness, preparedness and capacities for teachers and parents of children with special needs to be flexible, creative and ready to deliver quality teaching and learning during emergencies, bearing in mind that there is no single initiative that fits all emergencies